The Role of Education in Instilling People's Economic Values (4th Principle) for the Development of Micro, Small, and Medium Enterprises (MSMEs) - Abdul Muhaemin; Dimas Bagus Ferdiyanto; Mochamad Ray Akbarayaldi; Reihan Pratama; Dedy Yansyah (EDUJAVARE: International Journal of Educational Research, 2026)
Education plays a crucial role in shaping people's economic mindsets and behavior. This study aims to analyze the role of education in instilling people's economic values ​​based on the fourth principle of Pancasila as an effort to develop MSMEs, particularly in shaping public economic awareness, increasing the capacity of business actors, and strengthening economic practices oriented towards togetherness, participation, and shared prosperity. This study uses a qualitative approach with a literature study method (library research) through a review of various sources such as books, scientific journal articles, previous research, and relevant documents related to education, people's economy, Pancasila values, entrepreneurship, and MSME development. Data analysis was conducted using content analysis techniques through the processes of identification, grouping, interpretation, and drawing conclusions. The results of the study indicate that education has a strategic role in internalizing people's economic values ​​by forming an entrepreneurial character based on deliberation, responsibility, cooperation, creativity, and social concern. Education not only improves the technical capabilities of MSME actors in managing businesses but also builds awareness that economic activities must be directed towards the benefit of society and shared prosperity. The conclusion of this study confirms that Pancasila-based education is an important foundation in strengthening the development of MSMEs as part of the implementation of a democratic, inclusive, and sustainable people's economy.